(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Introduction: Tubal ectopics if large, uncontrollably bleeding or severely damaged need radical surgery (salpingectomy), otherwise conservative surgery (salpingotomy, salpingostomy) is the way of operative management. Laparoscopic surgery usually done in case of haemodynamically stable condition. Objective: To explore the different ways of surgical management of ectopic pregnancy in a tertiary care hospital. Materials and methods: This cross sectional study was carried out in the Department of Obstetrics and Gynaecology, Shaheed Suhrawardy Hospital and Dhaka Medical College Hospital during August 2005 and June 2006. The study population consisted of 50 women with ectopic pregnancy. Selected women underwent meticulous history taking and physical examinations. Some investigations like ultrasonography, culdocentesis, urine for pregnancy tests were done. Patients were treated by either radical or conservative surgery. Results: All (100%) women had abdominal tenderness. Ectopic pregnancy was diagnosed by history, physical examination and culdocentesis (84%), ultrasonography (12%) and laparotomy (4%). Two (4%) women were treated by conservative surgery, while the rest by radical surgery; 40 (80%) underwent unilateral salpingectomy, 3 (6%) unilateral salpingectomy with contralateral tubectomy, 2 (4%) unilateral salpingo oophorectomy, 1 (2%) total abdominal hysterectomy and 2 (4%) resection of rudimentary horn. Conclusion: Most common diagnostic tools were by history, physical examination and culdocentesis and common management was unilateral salpingectomy. Bangladesh J Obstet Gynaecol, 2013; Vol. 28(1) : 21-25